The racialisation of names: names and the persistence of racism in the UK - Wykes, Emily Jay (2013)
This thesis argues that despite claims that the UK is a post-racial society, (sur)names are understood in a racialised way. 31 semi-structured interviews and one survey-based interview were conducted. 29 of the 32 participants had changed their surname from one they perceived to be symbolically representative of their own embodied racial identity to one that they felt was not, or vice versa. This thesis claims that some (sur)names are socially constructed as invisible and normal, i.e. white British, whilst ‘Other’ names are deemed foreign and highly conspicuous. It is asserted that (sur)names inform stereotypes of a person’s embodied racial appearance. The confusion and intense interest encountered by the name-changers in relation to a perceived disjuncture between their embodied racial identity and the racialised categorisation of their name, exposes processes of racialisation. Name, embodied racial appearance and accent interact in different ways and contexts in deciding how a person is racialised and what their access is to the privilege associated with the majority identity of white Britishness. It is suggested that names are racially hierarchized according to the racial and/or national identity that the name is seen to represent. The thesis uses literature on race, racism, whiteness, racial passing, inbetween people and nationalism, in order to explore the racist and nationalist undertones of many participants’ encounters in regard to a racial disjuncture between name and body. Whilst supporting the point that race is a social construction rather than biological fact, the thesis nonetheless asserts that difference is conceived not just in terms of culture but in relation to embodied notions of race. Names should be acknowledged as being an important marker of biological conceptions of race. Race is still common currency in the UK, and this matters because power is differentially attributed within racialisation processes. Racism is not over.